Effect of the renin angiotensin system inhibitors on inflammatory markers: a systematic review and meta-analysis of 32 randomized controlled trials. (14th October 2021) - Awad, K; Zaki, M M; Mohammed, M; Banach, M
Abstract: Background: Inflammation plays a critical role in the etiology of cardiovascular disease (CVD). The renin-angiotensin system inhibitors including angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) have been shown to be effective in reducing elevated blood pressure. However, the information on their potential effect on inflammatory markers including C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) is still lacking. Purpose: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to synthesize evidence about effect of ACEIs and ARBs on selected inflammatory markers. Methods: PubMed, Scopus, and Embase were searched from inception until February 15, 2021. We included RCTs that assessed the effect of ACEIs or ARBs, compared with placebo, on any of the following markers: CRP, IL-6, or TNF-α. Mean changes in the relevant markers levels were pooled as a standardized mean difference (SMD) with a 95% confidence interval (CI) under the random-effects model. Heterogeneity was assessed using I 2 and χ 2 tests. Results: Thirty-two RCTs (n=3, 403 patients) were included in the analysis. Overall pooled analysis suggested that ACEIs significantly reduced plasma levels of CRP (SMD: −1.08 [95% CI: −1.57 to −0.59]; I 2 : 95%), IL-6 (SMD: −0.75 [95% CI: −1.41 to −0.09]; I 2 : 81%), and TNF-α (SMD: −1.77 [95% CI: −2.82 to −0.73]; I 2 : 95%). This lowering effect remained statistically significant by perindopril in terms of all relevant markers, by quinapril and ramipril in terms of IL-6 and by enalapril in terms of TNF-α. As for the ARBs as a class, they showed a statistically significant reduction only in terms of CRP (SMD: −0.14 [95% CI: −0.28 to −0.01]; I 2 : 0%) and did not significantly affect any of the other markers. Moreover, the ARBs individual drugs did not show any significant effect on any of the relevant markers except for valsartan that significantly reduced plasma levels of IL-6 (SMD: −0.42 [95% CI: −0.80 to −0.04]; I 2 : 0%). Conclusions: Based on the results of this meta-analysis, ACEIs showed a beneficial lowering effect on CRP, IL-6, and TNF-α, while ARBs were effective as a class only in terms of CRP reduction. Further larger RCTs are warranted to confirm these results particularly in case of individual drugs and to assess the significance of these reductions in terms of CVD prevention. Funding Acknowledgement: Type of funding sources: None.